Effects of Traditional Chinese Medicine for Vaginal Lavage Combined with Psychological Intervention in Postoperative Patients with Cervical Cancer. (15th December 2021) - Ma, Rufen; Yu, Ruixiang; Yuan, Yuchao; Ren, Baofeng; Li, Yuan
Abstract : Purpose . To explore the effects of traditional Chinese medicine for vaginal lavage combined with psychological intervention on the immune function and clinical efficacy in patients with cervical cancer. Methods . Patients with cervical cancer treated in our hospital from January 2020 to May 2021 were included in this study. All patients were treated with traditional Chinese medicine for vaginal lavage combined with psychological nursing intervention. The treatment outcomes of the patients were observed, and the quality-of-life scores and depression of the patients before and after treatment were compared. Changes in T-lymphocyte subset-related indicators, changes in blood routine-related indicators, and changes in the detection level of tumor markers were compared with anxiety scores. Results . After treatment, depression and anxiety were significantly reduced and the patient's quality of life significantly improved. After treatment, the patient's CD3 +, CD4 +, and CD4 + /CD8 + proportions were dramatically higher than before treatment (P < 0.05 ), there was no significant difference in CD8 + proportion before and after treatment (P > 0.05 ), and the white blood cell (WBC), hemoglobin (Hb), platelet (PLT) of patients, and the level of tumor marker (CA125) after treatment were immensely lower than before treatment (P < 0.05 ). Conclusions . Treating patients with cervical cancer with traditional Chinese medicine for vaginal lavage combined with psychological nursing can effectively improve the patient's immune function, effectively reduce the level of tumor marker CA125, increase the level of T-lymphocyte subsets, and improve the bone marrow hematopoietic function.